Evaluation of enterococci for potential probiotic utilization in dogs - Kubašová, Ivana; Lauková, Andrea; Hamarová, Ľudmila; Pristaš, Peter; Strompfová, Viola (Folia microbiologica, 2019)
Some strains of the genus Enterococcus are effective probiotic bacteria if they meet safety and probiotic criteria. In our study, 17 canine enterococci previously selected from a group of 160 isolates based on safety criteria were screened for some functional properties relevant to their use as probiotics. The results of antimicrobial resistance testing showed sensitivity of eleven strains to EFSA recommended antimicrobials. In contrast, the most frequent resistance was observed for cefotaxim (15/17) and oxacillin (13/17). PCR detection of resistance genes (vanA, vanB, vanC, tetM, tetL, ermB, and mefA) revealed the presence of mefA gene in five Enterococcus faecium strains and vanA gene in one strain. The production of enzymes commonly associated with intestinal diseases was in general rare (β-glucosidase 2/17, α-chymotrypsin 1/17, N-acetyl-β-glucosaminidase 0/17, and β-glucuronidase 0/17). The measurement of strain survival rate (%) under the conditions simulating gastric (pH 2.5) and bile juices (0.3% bile) showed considerable differences between strains (< 0.01 to 4.7% after 90 min for gastric juices, 48.0 to 254.0% after 180 min for bile). The concentration of produced L-lactic acid ranged between 83.1 to 119.3 mmol/L after 48 h cultivation depending on the strain. All strains fermented 16 out of 49 different carbohydrates (range from 17 to 23/49). Antimicrobial activity was recorded for two strains against some species of Listeria sp. and Enterococcus sp. Finally, two E. faecium candidates (IK25 and D7) were selected for testing in dogs, and hereafter they could possibly extend the currently limited range of beneficial bacteria of canine origin used as a dietary supplement for dogs.
Keywords: kyselina mléčná; Lactic Acid; zvířata; bakteriální léková rezistence; Carbohydrate Metabolism; Gastric Acid; Genes, Bacterial; Dogs; Enterococcus; psi; probiotika; Probiotics; Bacteriocins; Animals; žaludeční kyselina; Drug Resistance, Bacterial; Bile; bakteriociny; bakteriální geny; mikrobiální testy citlivosti; antibakteriální látky; Anti-Bacterial Agents; Microbial Sensitivity Tests; Bacteria; metabolismus sacharidů; žluč